The macroeconomics effects of the implementation of the euro in Poland in relation to the experience of other countries - Bajan Bartlomiej (Institute of Economic Research (IER), 2016)
In the chapter attempts have been taken to assess the potential impact of Polish accession to the euro zone. The analysis covers costs and benefits of monetary integration which are mostly pointed in literature, alluding to the experience of European Union countries. The analysis covers the years 1996-2004. A comparison was made between countries which have adopted the euro in 1999, and those that remained with the national currencies. There are differences between these two groups of countries in increments of GDP per capita, since the introduction of the euro in paper form, despite an earlier convergence of this indicator, however much smaller differences occurred in the case of the inflation rate. Both groups of countries have recorded a significant increase in foreign trade turnover since the inception of the euro area. The data used in the analysis come from the European Statistical Office (Eurostat) and the United Nations Conference on Trade and Development (UNCTAD).
Keywords: E02; E52; E59; F45; 330; monetary union; euro zone